Faktor-faktor yang berhubungan dengan praktik pemberian ASI eksklusif pada bayi usia 0-6 bulan di Kabupaten Timor Tengah Selatan - Ari Tri Astuti; Hamam Hadi; Madarina Julia (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2019)
Factors associated with exclusive breastfeeding practice among infants aged 0-6 months in Timor Tengah Selatan DistrictBackground: The health profile of Indonesia in 2018 indicated only 68,74% of infants were exclusively breastfed. East Nusa Tenggara is one of the provinces with lower exclusive breastfeeding coverage than national data in 2018 with only 52,67%. A survey in Timor Tengah Selatan district showed that exclusive breastfeeding also decreased from 2015 and 2016 which was 63.3% to 59.1%. Several factors have been known to be associated with exclusive breastfeeding practice, such as mother’s education and occupation, household expenditure, antenatal care history, and husband’s support.Objective: To identify factors associated with exclusive breastfeeding practice among infants aged 0-6 months in Timor Selatan District, East Nusa Tenggara province.Methods: An observational study with a cross-sectional design was conducted among 155 lactating mothers of infants aged 0-6 months. The secondary data from